Educators’ needs and perceived readiness for teaching in a pandemic emergency / Johan Eddy Luaran and Jasmine Jain - Luaran, Johan Eddy; Jain, Jasmine (UiTM Press, 2021)
The Covid-19 outbreak has forced teachers in Malaysia to abruptly shift from face-to-face teaching to online teaching. To teach online and to ensure lesson learning outcomes were met, it is vital for the teachers to be prepared with online teaching competencies. Due to this scenario, the objectives of this study are: (1) To investigate teacher’s readiness in online teaching based on their online teaching competencies, (2) To identify demographic factors that are related to teacher readiness in online teaching, and (3) To determine what are the teachers’ needs for them to be ready with online teaching competencies. There are 4 dimensions of online teaching competencies which are (1) Instructional Design, (2) Communication, (3) Time Management, (4) Technology Proficiency. The demographic factors that were identified in this research are (1) Gender, (2) Academic Rank, (3) Education Level, (4) Years of Teaching. This research used a quantitative approach involving a sample of 226 primary school academics in the district of Kuala Selangor, Selangor where they were asked to complete a questionnaire. The findings revealed that teachers have a high level of readiness in online teaching resulting in a mean value of (mean=3.67). However, it was also found that despite their high level of online teaching readiness, the teachers feel that they could achieve better outcomes if they have gone through techno-pedagogy related trainings, and if they are provided with better internet connectivity.